KEBIJAKAN FORMULASI SANKSI PIDANA TERHADAP PELAKU TINDAK PIDANA KORUPSI - Megawati Megawati; Madiasa Ablisar; Marlina Marlina; Suhaidi Suhaidi (USU LAW JOURNAL, 2014)
ABSTRACT   Policy formulation is a criminal sanction in formulating policies and establish criminal sanctions against the perpetrators of corruption. Legislation combating corruption establish criminal sanctions against offenders by determining the minimum criminal sanctions specifically, a higher penalty, and a sentence of death which is a criminal weighting and includes imprisonment for perpetrators of corruption. In the application of criminal sanctions against the perpetrators of corruption can be seen based on the formulation of the offense in article 2 and article 3, where the criminal sanctions imposed on the perpetrators of corruption, especially in some of the Medan District Court decisions are imprisonment, criminal penalties, and criminal confinement. Key words : criminal, sanction, corruption